Atividade ovicida e larvicida de óleos essenciais em Sarconesia chlorogaster (Diptera: Calliphoridae) - Porto, Bianca Carolina Zanardi (2016)
The parasitism by insects is a matter of great importance in tropical countries, where the climatic conditions favor their development. Among the parasites of importance we can highlight Diptera, such as flies, which because of their degree of sinantropismo are in direct contact with humans and animals. These insects have biontófagos and scavengers habits, highlighting species of Calliphoridae family, which cause economic loss to be veiculadoras of pathogens of major infectious diseases, parasitic and myiasis. Among the blowflies, the Sarconesia chlorogaster species, does not possess wide distribution, is described only in the south of the country and for that reason there are few studies about this insect. In this context, the aim of this study was to verify the action of seven essential oils [cinnamon (Cinnamomum zeylanicum), bergamot (Citrus bergamia), cedar (Cedrus atlantica), eucalyptus, ginger (Zingiber officinale), lemon grass (Cymbopogon citratus) and thyme (Thymus vulgaris)] against the eggs and larvae of this species of Diptera. To assess the in vitro efficacy was performed immersion test, where the eggs were immersed for five minutes in concentrations of 10, 20 and 40% and the larvae were immersed at 10 and 20%. In ovicidal activity tests, all essential oils showed efficacy greater than 75%, highlighting the thyme which showed 100% efficacy in the three concentrations tested. In larvicidal activity tests, thyme oil, cinnamon, ginger and cedar showed superior efficacy to 75% and bergamot oil, lemon grass and eucalyptus showed efficacy less than 50%. We can conclude that the essential oils can be an effective alternative for the control of diptera.